Breakout nations : in pursuit of the next economic miracles - Sharma, Ruchir (New Delhi, 2012)
In this bestselling critique of conven tional wisdom, writer and Morgan Stanley investor Ruchir Sharma draws on two decades spent touring the globe to offer insights into the world's most interesting emerging markets. Sharma reveals his rules for spotting success stories and lays out a compelling argument for where the future will happen. A new chapter written for this paperback edition explains what this means for rich nations of the West and whether we may be about to see an American economic renaissance. With the recent global economic crisis, the growth of the world's most celebrated and hyped emerging markets have witnessed a slowdown. The weaknesses of such emerging markets have often been overlooked in the hype and it is possible that the new breakout nations will probably be some of the low profile ones.
Keywords: International economics